2008
DOI: 10.1007/s00423-008-0436-x
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen and raloxifene improve metaphyseal fracture healing in the early phase of osteoporosis. A new fracture-healing model at the tibia in rat

Abstract: BackgroundFracture healing in osteoporosis is delayed. Quality and speed of fracture healing in osteoporotic fractures are crucial with regard to the outcome of patients. The question arises whether established antiosteoporotic drugs can further improve fracture healing.Materials and methodsOsteoporosis manifests predominantly in the metaphyseal bone. Nevertheless, an established metaphyseal fracture model is lacking. A standardized metaphyseal fracture-healing model with stable plate fixation was developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 36 publications
3
93
1
4
Order By: Relevance
“…We tried to mimic clinical situation the best, when a typical patient (female) with osteoporotic fracture, before being traumatized, suffers for years from post-menopausal changes in muscle and bone and receives no fracture preventive treatment (Haeussler et al 2007). Therefore, a metaphyseal osteotomy of tibia was performed after severe osteoporosis had been established (Wronski et al 1985, Stuermer et al 2008 and the animals received the substances orally to facilitate bone healing. Finally, the comparisons were made with osteoporotic rats either untreated serving as an osteoporotic control or properly treated with estrogen to meet the goal of the present experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tried to mimic clinical situation the best, when a typical patient (female) with osteoporotic fracture, before being traumatized, suffers for years from post-menopausal changes in muscle and bone and receives no fracture preventive treatment (Haeussler et al 2007). Therefore, a metaphyseal osteotomy of tibia was performed after severe osteoporosis had been established (Wronski et al 1985, Stuermer et al 2008 and the animals received the substances orally to facilitate bone healing. Finally, the comparisons were made with osteoporotic rats either untreated serving as an osteoporotic control or properly treated with estrogen to meet the goal of the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Soy proteins were substituted by potato proteins to eliminate an estrogenic effect of isoflavones presented in soy. After 8 weeks, when osteoporosis was established (Kalu 1991), a metaphyseal osteotomy and T-plate fixation of the tibiae was done under ketamine/xylazine anesthesia as described previously (Stuermer et al 2008). Along with anesthesia, rats received s.c. 5 mg Decentan (Merck) and 4 mg Rimadyl (Pfizer, Karlsruhe, Germany) per kg of BW respectively.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Furthermore, animal studies suggest the presence of estrogen will enhance fracture healing [31,51,55]. Both men and women experience lower estrogen levels as aging occurs [21], but the effects on bone quality may be more profound in men because of the lower likelihood of early diagnosis and primary prevention.…”
Section: Fracture Healingmentioning
confidence: 99%
“…Whilst estrogen treatment alone could induce dose dependent stimulation of both AP and NO production, tissue mineralization occurred only on the periphery of the callus explant without BMP-7 and cell proliferation was not as elevated. A previous report has shown that estrogen administration improved fracture healing in an ovarectomised rat model, where new tissue resembled healthy (non osteoporotic) bone and investigations showed that the estrogen suppressed genes associated with osteoblast and osteoclast activity (Stuermer et al 2010).…”
Section: Discussionmentioning
confidence: 94%